Depressed patients perception of the efficacy of electroconvulsive therapy and venlafaxine therapy - Kopecek, Miloslav; Cerná, Lubica; Sulak, Jan; Raszka, Michal; Bares, Martin; Seifertová, Dagmar (Neuro endocrinology letters, 2007)
BACKGROUND: The aim of our study was to evaluate the efficacy of electroconvulsive (ECT) and venlafaxine therapy from the patient's point of view. METHODS: We used a retrospective chart review from 22 inpatients who underwent ECT and 22 patients treated with venlafaxine due to resistant unipolar or bipolar depression. We used bilateral ECT in a median of 8 (IQR 7-9.7) sessions and venlafaxine therapy with a median daily dosage of 225 mg (IQR 150-225 mg) for a median of 4 (IQR 4-5) weeks. The main outcome was change in a self-evaluation scale - Short Form of the Beck Depression Inventory (BDI-SF). The response was defined as the decreasing of the BDI-SF score by >or=50%, remission as decreasing of BDI-SF score <or=4. RESULTS: We did not find significant differences between sex, age and BDI-SF before therapy in both groups. The reduction of BDI-SF score was significantly higher in the ECT group than in venlafaxine group (p=0.025). Significantly more patients treated with ECT reached response than patients treated with venlafaxine (68% vs. 23%; <0.01). The remission rate after ECT was not significantly higher than venlafaxine therapy (27% vs. 5%; p=0.094). The number needed to treat (NNT) of ECT for BDI-SF response was 3 (CI95% 1.4 to 5.2) and NNT for BDI-SF remission was 5 (CI95% 2.3 to 45.8). DISCUSSION: After the median of 3 failed antidepressant trials, ECT was more effective than venlafaxine in the short term therapy in some parametres according to our patients. We suggest that the fact that mental state was evaluated by patients themselves is an important pro-argument in the discussion about ECT.
Keywords: výsledek terapie; cyklohexanoly; spokojenost pacientů; Male; elektrokonvulzívní terapie; retrospektivní studie; Self-Assessment; Electroconvulsive Therapy; Adult; dospělí; mužské pohlaví; Patient Satisfaction; venlafaxin hydrochlorid; depresivní poruchy; Severity of Illness Index; antidepresiva druhé generace; Treatment Outcome; Cyclohexanols; lidé; ženské pohlaví; Humans; Depressive Disorder; stupeň závažnosti nemoci; Retrospective Studies; Venlafaxine Hydrochloride; psychiatrické posuzovací škály; sebezhodnocení (psychologie); Female; Antidepressive Agents, Second-Generation; lidé středního věku; Psychiatric Status Rating Scales; Middle Aged